1967
DOI: 10.1039/j39670000665
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenic nitrogen compounds. Part LVII. Hexacyclic acridines derived from phenanthrene and fluorene

Abstract: The use of 9-and 2-aminophenanthrene for the preparation of tribenzo-and benzonaphtho-acridines and related heterocycles has been investigated : with 2-aminophenanthrene, the site of the acridine cyclisations is shown to be position 1. Benzoindenoacridines isosteric with benzonaphthoacridines were prepared from 4-aminofluorene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1970
1970
2011
2011

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Chromeno [4,3-b]quinolin-6-one derivatives (3a-n) are important class of chromeno-quinolines and the most conventional approach for their synthesis involves the reaction of 4-hydroxycoumarins with anilines and paraformaldehyde at 220-240 • C under vacuum. 19 Tabakovic et al have reported their synthesis starting from 4-hydroxycoumarin under Vilsmeier-Haack conditions. 20 Asherson et al have reported their synthesis from 3-((dimethylamino)methyl)-4-hydroxy-2Hchromen-2-one and anilines but with lower yields.…”
Section: Resultsmentioning
confidence: 99%
“…Chromeno [4,3-b]quinolin-6-one derivatives (3a-n) are important class of chromeno-quinolines and the most conventional approach for their synthesis involves the reaction of 4-hydroxycoumarins with anilines and paraformaldehyde at 220-240 • C under vacuum. 19 Tabakovic et al have reported their synthesis starting from 4-hydroxycoumarin under Vilsmeier-Haack conditions. 20 Asherson et al have reported their synthesis from 3-((dimethylamino)methyl)-4-hydroxy-2Hchromen-2-one and anilines but with lower yields.…”
Section: Resultsmentioning
confidence: 99%
“…[32P]P1 with the terminal phosphate of ADP (Grunberg-Manago et al 1956;Thang, 1967). The reaction mixture (0.lml) contained: tris-HCI buffer, pH8.0, lOu.tmol;…”
Section: Methodsmentioning
confidence: 99%
“…The discovery afforded a probable explanation for the lack of reproducibility (Ochoa, & Mii, 1961;Ochoa, Krakow & Basilio, 1963) and low yield (Thang, 1967) of the published purification procedures and made possible the development of an effective method for the isolation in good yield of highly purified A. vinelandii polynucleotide phosphorylase in its reduced form.…”
mentioning
confidence: 99%